Ideal Interactions: Perspectives of Parents and Teachers of Children With Autism Spectrum Disorder - Azad, Gazi (Sch Comm J, 2018)
We conducted a qualitative study using key informant interviews with 18 teachers and 39 parents of children with autism spectrum disorder (ASD) about how they would envision their ideal interactions with each other. Four main themes emerged from our content analysis. Parents and teachers were concerned about different aspects of communication with each other. Neither party wanted to ask the other for more involvement, and both attributed resistance to a lack of confidence in their expertise. Parents and teachers valued parental presence, but teachers wanted parents to be active partners in the education of their children. The results suggest possible reasons why parents and teachers of children with ASD are often dissatisfied with their interactions. Discussion centers on similarities and differences with general education, as well as on practical solutions to promote more positive exchanges between parents and teachers of children with ASD in school-based contexts.